Costs of housing crises: International evidence - Christian Aßmann; Jens Boysen-Hogrefe; Nils Jannsen (Kiel Institute for the World Economy (IfW), 2011)
This paper analyzes the costs of housing crises in terms of GDP growth and the economic conditions under which crises are particularly costly. Housing crises are often followed by recessions that are longer than other recessions. According to empirical estimates, a housing crisis reduces the GDP growth rate in the following year on average by two percentage points and has still a considerable negative impact in the second year. One important channel through which the effect of housing crises is passed on seems to be the banking sector. In addition, our results suggest that negative wealth effects possibly cause further reductions in GDP.
Older version: http://hdl.handle.net/10419/28351
Keywords: E21; E32; C23; 330; Housing crisis; Panel Data; Immobilienmarkt; Branchenkrise; Konjunktur; Soziale Kosten; Industrieländer